Schizandrin B protects LPS-induced sepsis via TLR4/NF-κB/MyD88 signaling pathway - Xu, Jianjun (Am J Transl Res, 2018)
Schizandrin B (Sch B) is the main component isolated from Schizandra fruit (Schisandra chinensis). While Sch B is established as having antioxidant, anti-proliferation and anti-inflammatory properties, but its activity in sepsis remains unclear. In the present study, we investigated the anti-inflammatory effects of Sch B in sepsis. Our experimental results demonstrated that Sch B inhibited production of IL-1β, TNF-α, IL-6 and HMGB1 by LPS-activated RAW264.7 cells. Moreover, Sch B suppressed expression of iNOS, reduced production of PGE2, blocked expression of MyD88 and TLR4, suppressed the activity of NF-κB and decreased phosphorylation of MAPKs in LPS-activated RAW264.7 cells. Administration of Sch B also reduced production of IL-1β and TNF-α, attenuated infiltration of inflammatory cells and tissue damage in lung, liver and kidney, and enhanced survival rate of LPS-challenged mice. Taken together, our data suggest that Sch B has anti-inflammatory properties against LPS-induced inflammation and sepsis. Sch B could protect against LPS-induced sepsis via the TLR4/NF-κB/MyD88 signaling pathway, and potentially be a novel anti-inflammatory and immunosuppressive drug candidate for treating sepsis.